1998
DOI: 10.1029/97gl02957
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of NOy on wave‐cloud ice particles

Abstract: Abstract. In a flight through a wave cloud during SUCCESS on 2 sampling opportunity since the particles are only minutes old and May 1996, simultaneous forward-and aft-facing NOy inlets were likely nucleated on sulfuric acid aerosols [Jensen et al., this issue]. used to infer the amount of condensed-phase NOy present on ice particles that were up to a few minutes old. Condensed-phase 2. Measurements amounts were 25-75 pptv, or 10-20% of gas-phase NOy. Given The "aft-inlet" NOy was sampled through a horizontal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 14 publications
2
49
0
1
Order By: Relevance
“…This conclusion is supported by field observations which have confirmed uptake of both HNO 3 and HO 2 NO 2 to snow surfaces Slusher et al, 2002), and of HNO 3 to cirrus clouds (Weinheimer et al, 1998;Popp et al, 2004;Ziereis et al, 2004). In general, therefore, in snow covered areas, or indeed regions of the atmosphere with lofted snow/ice, such as cirrus clouds or blowing/precipitating snow, physical adsorption of HNO 3 and HO 2 NO 2 from the air to the snow/ice is likely to occur.…”
Section: A E Jones Et Al: Ho 2 No 2 and Hno 3 In The Coastal Antarsupporting
confidence: 55%
“…This conclusion is supported by field observations which have confirmed uptake of both HNO 3 and HO 2 NO 2 to snow surfaces Slusher et al, 2002), and of HNO 3 to cirrus clouds (Weinheimer et al, 1998;Popp et al, 2004;Ziereis et al, 2004). In general, therefore, in snow covered areas, or indeed regions of the atmosphere with lofted snow/ice, such as cirrus clouds or blowing/precipitating snow, physical adsorption of HNO 3 and HO 2 NO 2 from the air to the snow/ice is likely to occur.…”
Section: A E Jones Et Al: Ho 2 No 2 and Hno 3 In The Coastal Antarsupporting
confidence: 55%
“…Cirrus clouds, for example, are radiatively important in the atmosphere and also provide surfaces for heterogeneous reactions. Laboratory studies have shown that HNO 3 can be taken up by ice surfaces at tropospheric temperatures (e.g., Hudson et al, 2002) and observations of uptake of HNO 3 by cirrus are accumulating (e.g., Weinheimer et al, 1998;Popp et al, 2004;Ziereis et al, 2004). A long-standing issue within atmospheric chemistry is that numerical models generally overestimate HNO 3 /NO x ratios in the upper troposphere (e.g., Chatfield, 1994;Brunner et al, 2005).…”
Section: Global/regional Impacts: Modeling Assessment and Observationsmentioning
confidence: 99%
“…The interaction of HNO 3 and cirrus ice crystals was investigated experimentally during several field campaigns from the tropics to the Arctic (Weinheimer et al, 1998;Schlager et al, 1999;Kondo et al, 2003;Popp et al, 2004;Ziereis et al, 2004;Voigt et al, 2006). Voigt et al (2006) summarized these measurements in terms of average nitric acid to water molar ratios (µ=HNO ice 3 /H 2 O ice ) in cirrus ice particles and ice-bound fractions of total nitric acid (φ =HNO ice 3 /HNO tot 3 ).…”
Section: Introductionmentioning
confidence: 99%